Carbonea tephromelae M. Svensson & M. Westb. 2021, sp. nov. - Svensson, Måns; Westberg, Martin (Zenodo, 2021)
Carbonea tephromelae M.Svensson & M.Westb. sp . nov . Fig. 2A–2E MycoBank No: MB840305 Holotype:— SWEDEN. Lule lappmark: Jokkmokk par., Padjelanta National Park, 11 km WNW of Staloluokta, S slope of Unna Duvgge (Unna Toki), c. 460 m NE of small cabin, 67.34787˚N, 16.45453˚E, elev. 703 m, S-exposed slope in bare mountain region, on Tephromela atra on rock, 5 August 2020, Martin Westberg PAD384 (UPS L-994014). Diagnosis :—Distinguished from other Carbonea species with a colourless hypothecium by having globose to broadly ellipsoid spores and by growing on Tephromela atra . Etymology :—Named after its host species Tephromela atra (Huds.) Hafellner. Description :—Lichenicolous fungus. Thallus inapparent, inhabiting the thallus of Tephromela atra , which darkens and is apparently damaged due to the infection (Fig 2A). Apothecia black, shining, c. 0.2–0.4(–0.5) mm diam., rounded to flexuose, sessile on the thallus of the host. Disc flat or becoming somewhat convex in larger apothecia. Proper exciple concolorous with the disc, persistent, narrow, raised or level with the disc in older apothecia. Apothecial anatomy: Proper exciple opaque, appearing black even in thin sections, densely pigmented blue-green (Cinereorufa-green sensu Meyer & Printzen 2000) in the upper part, in the lower part beneath the hypothecium in mixture with a dark brown pigment, c. 20–45(–85) µm thick, composed of radiating, thick-walled hyphae with c. 2 µm wide lumina. Hymenium colourless or faintly blue-green, c. 50–75 µm tall. Epihymenium strongly blue-green (Cinereorufa-green), N+ red, K−. Hypothecium colourless, without visible crystals in polarized light. Paraphyses simple or forked near the tips, septate and often slightly constricted at the septa, c. 1.5 µm in midhymenium, tips colourless, cylindrical to clavate, 1.5–2.5 µm wide. Asci of Lecanora - type, 8-spored, clavate, 41–49 × 12–19 µm. Ascospores broadly ellipsoid to globose, (7.5–)8.66 ±0.97(–11) × (5.5–)6.81 ±0.71(–8.5) µm; l/b ratio (1–)1.28 ±0.2(– 1.67) (n=57). Distribution ...